2022
DOI: 10.1093/ejcts/ezac380
|View full text |Cite
|
Sign up to set email alerts
|

Histological and structural effects of biodegradable polydioxanone stents in the rabbit trachea

Abstract: Objectives The aim of this study was to evaluate the potential biologic effects caused by successive placement of biodegradable polydioxanone (PDO) stents in the rabbit trachea. PDO stents could eventually induce a fibroproliferative reaction in the submucosa that could be beneficial in the treatment of malacia due to an increase in its consistency without impairing the tracheal lumen. Methods Sixteen adult NZ rabbits were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Hyperplasia of goblet cells resulting in hypersecretion was also observed [ 2 ]. Valverde et al [ 22 ] showed that successive stenting caused mild inflammatory changes in the tracheal wall and no increase in the collagen matrix or modifications in the cartilage structure. Generally, the response to damage is the formation of granulation tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperplasia of goblet cells resulting in hypersecretion was also observed [ 2 ]. Valverde et al [ 22 ] showed that successive stenting caused mild inflammatory changes in the tracheal wall and no increase in the collagen matrix or modifications in the cartilage structure. Generally, the response to damage is the formation of granulation tissue.…”
Section: Discussionmentioning
confidence: 99%
“…70,124,125 Given the persistent good mechanical properties, machinability, non-antigenity, low inflammatory reaction, and predictable degradation rate, it has been widely used in various medical applications, such as sutures, drug carriers, airway stents, biliary stents, tissue engineering scaffolds. 51,124,[126][127][128][129][130][131] Both the Pansy occluder and Memsorb occluder used PDO as the skeleton material, and clinical trial results were satisfactory. 51,52,[68][69][70][71][72] The complete degradation took around 6-24 months, and the loss of support strength was slow during degradation, hence, it could provide good support for 5-6 weeks.…”
Section: Polydioxanonementioning
confidence: 97%
“…Compared with other biodegradable polymers, like PGA and PLA, PDO produces less acidic products, elicits weaker inflammatory reactions, and has better flexibility and tensile strength 70,124,125 . Given the persistent good mechanical properties, machinability, non‐antigenity, low inflammatory reaction, and predictable degradation rate, it has been widely used in various medical applications, such as sutures, drug carriers, airway stents, biliary stents, tissue engineering scaffolds 51,124,126–131 …”
Section: Application Of Biodegradable Polymers In Absorbable Cardiac ...mentioning
confidence: 99%
“…reported the successful application of poly (L‐lactide‐ co ‐ ε ‐caprolactone) (PLCL) and PLGA loaded with rapamycin to inhibit fibroblast proliferation and collagen generation in mouse models. [ 16–20 ] Paunović et al. described a 3D printed poly (D, L‐lactide‐ co ‐ ε ‐caprolactone)‐based airway stent with excellent mechanical properties, biocompatibility, and degradation characteristics comparable to the advanced commercial silicone stents.…”
Section: Introductionmentioning
confidence: 99%
“…[4,15] The safety and efficacy of polydioxanone stents have been evaluated in animal models and the clinic, while Duvvuri et al reported the successful application of poly (L-lactide-co-𝜖-caprolactone) (PLCL) and PLGA loaded with rapamycin to inhibit fibroblast proliferation and collagen generation in mouse models. [16][17][18][19][20] Paunović et al described a 3D printed poly (D, L-lactide-co-𝜖caprolactone)-based airway stent with excellent mechanical properties, biocompatibility, and degradation characteristics comparable to the advanced commercial silicone stents. [21] Zhu et al reported a PLCL-based airway stent eluted with mitomycin in a spiral or tubular form for the prevention of tracheal stenosis.…”
Section: Introductionmentioning
confidence: 99%